Antenatal care an investigation of the time interval between the confirmation of pregnancy diagnosis and commencement - Moshokwa, Molatelo Linneth (Department of Obstetrics and Gynaecology, 2019)
Introduction This study aimed to investigate the time interval between the confirmation of pregnancy diagnosis and the commencement of antenatal care at the Metro West district of Cape Town, and to explore reasons for delays between the confirmation of pregnancy and the first antenatal booking. Methods A cross sectional descriptive study was conducted in September 2015 at Vanguard MOU, in which 120 pregnant women were interviewed at their first antenatal visit, using a structured questionnaire. Subjects were grouped into those with a short time interval (less than 60 days) between confirmation of pregnancy diagnosis and booking, and those with a long time interval (more than 60 days). The two groups were compared. The study hypothesis was that income would be a significant determinant of this time interval. The data were divided into descriptive and categorical variables. A logistic regression analysis was conducted to determine the association between independent variables and the dependent variable (time interval). Results The average gestational age at confirmation of pregnancy was 10.75 ± 5.88 weeks and the average gestation at booking was 18.27 ± 7.27 weeks. The mean time interval between confirmation of pregnancy diagnosis and first antenatal visit was 7.50 ± 6.63 weeks. Seventy- three (60.83%) reported a short time interval (SI) while 47 (39.17%) reported a long time interval (LI). The prevalence of late booking (defined as booking at or after 20 weeks) in the total study sample was 38.30%. There was a significant association between late attendance and LI with 70.21% of the LI group attending late, as compared to 17.81% of the SI group (OR 10.88; 95% CI 4.23-28.43). The time interval was significantly influenced by the women’s type of residence, the perception of the women regarding knowledge of the timing of antenatal care, and perception of the timing of pregnancy complications. It was not influenced by monthly income, thus refuting our hypothesis. Previous obstetric complications did not influence the time interval. Private confirmation of pregnancy by a general practitioner or home pregnancy test was significantly associated with a long interval; 37 (78.7%) in the LI group compared to 43 (59.9%) in the SI group, (p= 0.016). Reasons for the delay in booking were mostly related to poor understanding by women of the role of antenatal care and the ideal time of booking. Discussion and Conclusion Even though some women confirm their pregnancy as early as three weeks, there were notable delays in booking for their first antenatal visit, thus delaying antenatal care. However, the time delays seemed shorter than found in the previous Cape Town study, and compared to other studies in Africa. Many women perceived antenatal care to be curative rather than preventive. It is suggested that the site where women confirm their pregnancy (pharmacy, general practitioner or family planning clinic) should refer women immediately for antenatal booking. Also antenatal care sites should offer pregnancy testing services so that booking could occur after pregnancy is confirmed on the same day and at the same site.